Comparison of motor diagnoses by Chicago Classification versions 2.0 and 3.0 on esophageal high‐resolution manometry. Issue 7 (23rd February 2017) - Patel, A.; Cassell, B.; Sainani, N.; Wang, D.; Shahid, B.; Bennett, M.; Mirza, F. A.; Munigala, S.; Gyawali, C. P.
Abstract: Background: The Chicago Classification (CC) uses high‐resolution manometry (HRM) software tools to designate esophageal motor diagnoses. We evaluated changes in diagnostic designations between two CC versions, and determined motor patterns not identified by either version. Methods: In this observational cohort study of consecutive patients undergoing esophageal HRM over a 6‐year period, proportions meeting CC 2.0 and 3.0 criteria were segregated into esophageal outflow obstruction, hypermotility, and hypomotility disorders. Contraction wave abnormalities (CWA), and 'normal' cohorts were recorded. Symptom burden was characterized using dominant symptom intensity and global symptom severity. Motor diagnoses, presenting symptoms, and symptom burden were compared between CC 2.0 and 3.0, and in cohorts not meeting CC diagnoses. Key Results: Of 2569 eligible studies, 49.9% met CC 2.0 criteria, but only 40.3% met CC 3.0 criteria ( P <.0001). Between CC 2.0 and 3.0, 82.8% of diagnoses were concordant. Discordance resulted from decreasing proportions of hypermotility (4.4%) and hypomotility (9.0%) disorders, and increase in 'normal' designations (13.0%); esophageal outflow obstruction showed the least variation between CC versions. Symptom burden was higher with CC 3.0 diagnoses ( P ≤.005) but not with CC 2.0 diagnoses ( P ≥.1). Within 'normal' cohorts for both CC versions, CWA were associated with higher likelihood of esophageal symptoms, especially dysphagia, regurgitation, and heartburn, compared to truly normal studies ( P ≤.02 for each comparison). Conclusions and Inferences: Despite lower sensitivity, CC 3.0 identifies esophageal motor disorders with higher symptom burden compared to CC 2.0. CWA, which are associated with both transit and perceptive symptoms, are not well identified by either version. Abstract : Diagnostic criteria for motor diagnoses are different between Chicago Classification (CC) 2.0 and 3.0. We evaluated over 2500 studies using both sets of diagnostic criteria. CC 3.0 is less sensitive in identifying motor diagnoses, but selects out conditions associated with higher symptom burden compared to CC 2.0. Abnormalities in the contraction wave are not well identified by both CC versions, and therefore a 'normal' designation on CC remains compatible with contraction wave abnormalities (CWA). We demonstrate that CWA are clinically relevant, are associated with a higher likelihood of esophageal symptoms compared to true normal studies, and may need to be recognized before designating a manometric study as normal.